Oil price and oil price volatility as explanatory factors on green bond prices - Kinos, Pauliina (My University, 2023)
To keep the rise of global average temperature below 2°C, the Paris Agreement was signed by almost 200 state parties in 2015. Due to the agreement, the question arose, how these goals will be achieved. It has been stated that achieving the goals set in the agreement, green investments worth of trillions are needed of which about 70% are targeted for primary energy and energy efficiency investments. Green bonds have been stated to be the best instrument for allocating the financing for the projects and since the first one launched in 2007, the green bond market has increased enormously. Due to the great part of the green financing is needed in energy related investments, is green bond market somewhat tied to other energy market. It has been suggested that the relationship between green bonds and oil, which presents a traditional energy source, is substitutive. In other words, it has been stated that high oil price would encourage seeking other options and therefore boost the demand of renewable energies and further green financing and vice versa. These price dynamics have been studied previously mainly from stock price perspectives while only few researchers have been focusing to green bond price perspective. The purpose of this study is to investigate the substitutive relationship between oil and green bonds. The study aims to answer questions like does the oil price have explanatory power to green bond price development, and whether the relationship is positively or negatively correlated. Similar hypotheses are determined for OVX (Oil Volatility Index) as well, which aims to answer to questions like does oil price volatility explain green bond price developments and if their relationship is positively or negatively correlated. This study is quantitative study using deductive logic. The hypotheses are tested with multiple linear regression analysis, which was chosen as a method as it is commonly used methodology in quantitative research investigating interactions between different variables. The data is collected from Bloomberg and DataStream during January and February 2023 conducting a final data set of eight variables with sample size of 1463 observations per variable. The observations are daily closing prices from trading days. The result of the analysis supports existing literature as it shows that oil prices do have explanatory power of green bond prices and that their relationship is negative. Increase of one unit in oil price causes a decline of 0.016 unit in green bond prices. In turn, despite the existing literature, the study did not support the explanatory relationship between oil price volatility and green bond prices. However, it must be noted that the data of the OVX had a high kurtosis despite the data transformations and therefore it had a poor fit to the model, which is why the results regarding the relationship between the OVX and green bond prices must be observed critically. Therefore, understanding the price dynamics between the oil prices and green bonds is an important finding for both issuers and investors. Also, given that one of the largest demands of green financing is faced in the field of transportation, the importance of this topic to supply chains is undeniable.

Pariisin ilmastosopimuksen agendana on ilmastonlämpenemisen pysäyttäminen alle 2°C ja se allekirjoitettiin lähes 200 osapuolen kesken vuonna 2015. Sopimuksen siivittämänä kysymykset tavoitteiden saavuttamiskeinoista nousivat ilmoille. Tavoitteisiin pääseminen edellyttää miljardien edestä vihreitä investointeja, joista noin 70 %:ia tulisi kohdentaa energia ja energia tehokkuus sektoreille. Vihreiden joukkolainavelkakirjojen (engl. green bond), jotka lanseerattiin vuonna 2007, on esitetty olevan paras instrumentti rahoituksen allokoimiseen vihreille investoinneille ja projekteille. Vihreät joukkovelkakirjat ovat osittain sitoutuneita energia markkinaan, sillä suuri osa niillä rahoitettavista projekteista ja investoinneista osuvat kyseiselle sektorille, kuten esitetty ilmastotavoitteiden pääsemisen yhteydessä. On esitetty, että vihreät joukkovelkakirjat ovat substituuttisessa suhteessa öljyyn nähden, joka edustaa perinteistä fossiilista energianlähdettä. Toisin sanoen, öljyn hinnan nousu tarkoittaisi sille substituuttisten uusiutuvien energioiden kysyntää ja siten niihin investointia ja vihreän rahoituksen tarvetta. Substituuttista suhdetta on aikaisemmin tutkittu pääasiassa vihreiden osakkeiden ja öljyn suhteen, kun vain pieni osa kirjallisuudesta on keskittynyt vihreisiin joukkovelkakirjoihin ja öljyyn. Tämän tutkimuksen tarkoitus on tutkia tätä substituuttista suhdetta öljyn ja vihreiden joukkovelkakirjojen välillä. Tutkimus pyrkii vastaamaan kysymyksiin, kuten onko öljyn hinnalla selittävä vaikutus vihreiden joukkovelkakirjojen hintakehitykselle, entä onko öljyn hinnan volatiliteetilla, eli OVX (Oil Volatility Index) mittarilla, vaikutusta vihreiden joukkovelkakirjojen hintoihin. Tutkimus on kvantitatiivinen ja deduktiivinen tutkimus. Hypoteeseja, joita on kuusi yhteensä, testataan lineaarisella regressioanalyysilla, joka valikoitui tutkimuksen metodiksi sen suosittavuuden takia tutkimuksessa, joissa tutkitaan muuttujien välisiä yhteyksiä. Data kerättiin Bloomberg ja DataStream palveluista tammi- ja helmikuun 2023 aikana muodostaen seitsemän muuttujan aineistokokonaisuuden. Jokaisessa muuttuja-aineistossa havaintoja on 1463 kappaletta. Havainnot ovat sulkuhintoja kaupankäyntipäiviltä. Suurin osa tutkimuksen tuloksista puoltavat aikaisempia tutkimuksia ja kirjallisuutta. Tutkimus vahvistaa, että öljyn hinnalla on selittävä vaikutus vihreiden joukkovelkakirjojen hintakehitykselle niiden välisen suhteen ollessa negatiivinen. Tulos puoltaa substituuttista suhdetta. Puolestaan OVX:n ei havaittu selittävän vihreiden joukkovelkakirjojen hintoja, mikä ei puolla olemassa olevaa tutkimusta ja kirjallisuutta. Tulokseen on saattanut vaikuttaa muuttuja- aineiston huono istuvuus käytettyyn malliin ja sen olettamuksiin, jonka takia tulosta pitää havaita kriittisesti. Tulokset ja hintadynamiikan ymmärtäminen öljyn ja vihreiden joukkovelkakirjojen välillä ovat kinnostavia niin liikkeellelaskijoille, kuten sijoittajillekin. Lisäksi, koska suuri osa vihreistä rahoitustarpeista keskittyy kuljetuksiin, uusiutuviin energioihin ja energiatehokkuuden parantamiseen esimerkiksi tuotantolaitoksissa, on suhde vihreän rahoituksen ja energiaintensiivisen kuljetusalan välillä kiinnostavaa ja hyödyllistä ymmärtää.
Keywords: oil price, oil price volatility, green bond